Comparative risk assessment of non-communicable diseases by evacuation scenario- a retrospective study in the 7 years following the Fukushima Daiichi nuclear power plant accident - Shuhei Nomura; Michio Murakami; Akihiko Ozaki; Toyoaki Sawano; Claire Leppold; Yoshitaka Nishikawa; Hiroaki Saito; Tomoyoshi Oikawa; Masaharu Tsubokura (Taylor & Francis Group, 2021)
Background: As a result of the Fukushima Daiichi nuclear power plant accident, many residents evacuated and were exposed to changes in their living environment and socioeconomic status, and to persistent stressors. Past studies have suggested the potential for these circumstances to contribute to long-term changes to population health. Objective: The objective of this study was to gain a better understanding of long-term health effects of evacuation, by evaluating the risk of non-communicable diseases among evacuees from Minamisoma City (one of the closest municipalities to the power plant) until 2017. Methods: The study evaluated data from annual health check-ups for residents aged 40-74 years covered by National Health Insurance (who are largely self-employed) from 2010 to 2017 administered by Minamisoma City. Diabetes, hyperlipidemia, and hypertension were defined from the results of blood sampling. Annual changes in age-adjusted prevalence were estimated by evacuation scenario. We also performed an inverse-probability weighting (IPW) analysis to adjust for baseline covariates in 2010 and estimated the differences in the risk of diabetes, hyperlipidemia, and hypertension by evacuation scenario as of the 2017 health check-up in reference to the no-evacuation group. Results: A total of 1,837 individuals were considered in this study. Regardless of evacuation scenario, there was statistical evidence suggesting an upward and a downward trend in diabetes and hypertension from 2010 to 2017, respectively, while hyperlipidemia showed no remarkable change. IPW analyses demonstrated that disease risks in 2017 did not differ significantly among people with different evacuation scenarios. Conclusions: Region-specific factors played an important role in the health effects of the evacuation. Our findings have important implications for the need of an assessment of the health effects of evacuations in more localized manner. Further research in this area will strengthen the communities' preparedness for future disasters that require mass evacuation.